inverse function questions related to ordered pairs, linear, cubic root, square root, logarithmic and exponential functions are presented along with their detailed solutions. Answers are checked algebraically and graphically using the properties of a given function and its inverse. To be more effective, the questions need to be solved in order as each question makes it easier to understand the next.
Find the inverse of a function given as a set of ordered pairsQuestion 1a) Find the inverse of function f given by:f = {( -2 , 0) , (0 , 1) , (2 , 3) , (3 , 4)} b) Find the domain and range of the inverse. c) Let f^{ -1} be the inverse of f. Evaluate: f(f^{ -1}(0)) , f(f^{ -1}(1)) , f(f^{ -1}(3)) , f(f^{ -1}(4)) f^{ -1}(f(- 2)) , f^{ -1}(f(0)) , f^{ -1}(f(2)) , f^{ -1}(f(3)) d) Graph f and f^{ -1} on the same system of rectangular axes. Solution to Question 1a)The inverse of f is found by exchanging the input and output of the given function. Hence the inverse of f is given by f^{ -1} = {(0 , -2) , (1 , 0) , (3 , 2) , (4 , 3)} b) Domain of f^{ -1} = {0 , 1 , 3 , 4} Range of f^{ -1} = {-2 , 0 , 2 , 3} c) f(f^{ -1}(0)) = f (-2) = 0 f(f^{ -1}(1)) = f(0) = 1 f(f^{ -1}(3)) = f(2) = 3 f(f^{ -1}(4)) = f(3) = 4 f^{ -1}(f(- 2)) = f^{ -1}(0) = - 2 f^{ -1}(f(0)) = f^{ -1}(1) = 0 f^{ -1}(f(2)) = f^{ -1}(3) = 2 f^{ -1}(f(3)) = f^{ -1}(4) = 3 d) The graph of f (blue) and f^{ -1} (red) are shown below. Important: Note the following properties of f and its inverse f^{ -1}. 1) The graph of f is the reflection of the graph of f^{ -1} and the graph of f^{ -1} is the reflection of the graph of f on the line y = x. 2) The x and y intercepts on the graph of f becomes y and x intercepts, respectively, on the graph of f^{ -1} 3) The domain and range of f become the range and domain respectively of f^{ -1} 4) f(f^{ -1}(x)) = x and f^{ -1}(f(x)) = x 5) If function f is the inverse of function g then function g is the inverse of function f (a function and its inverse make a pair of functions)
Find the inverse of a linear functionQuestion 2Find the inverse of the linear function f(x) = 2x + 2 and graph f and its inverse in the same system of axes.Solution to Question 2How to find the inverse?step 1: Replace f(x) by y and rewrite the function as an equation as follows y = 2 x + 2 step 2: Exchange x and y in the above equation x = 2 y + 2 step 3: Solve the above equation for y 2 y = x - 2 y = (1/2) x - 1 Step 4: Write the inverse using the inverse function notation f^{ -1} (x) = (1/2) x - 1 Step 5: Check the answer obtained (using the properties : f(f^{ -1}(x)) = x and f^{ -1}(f(x)) = x ) One way to check the answer obtained is to make sure that f(f^{ -1}(x)) = x and f^{ -1}(f(x)) = x. f(f^{ -1}(x)) = 2(f^{ -1}(x)) + 2 = 2((1/2) x - 1) + 2 = x - 2 + 2 = x f^{ -1}(f(x)) = (1/2) f(x) - 1 = (1/2)(2 x + 2) - 1 = x + 1 - 1 = x The graphs of f and f^{ -1} are shown below and we can easily see that the graphs are reflection of each other on the line y = x. This is a graphical method to check whether a pair of functions are inverse of each other.
Find the inverse of a cube root functionQuestion 3Find the inverse of the function g(x) = ∛(x - 1) and graph f and its inverse in the same system of axes.Solution to Question 3step 1: Rewrite the function as an equation as follows y = ∛(x - 1) step 2: Exchange x and y x = ∛(y - 1) step 3: Solve the above equation for y Raise both sides of the equation to the power 3 and simplify (x)^{3 } = (∛(y - 1))^{3 } x^{3 } = y - 1 y = x^{ 3} + 1 Step 4: Use the inverse function notation to write g^{ -1} (x) = x^{ 3} + 1 Step 5: Check algebraically the answer (using the properties : f(f^{ -1}(x)) = x and f^{ -1}(f(x)) = x ) g(g^{ -1}(x)) = ∛(g^{ -1}(x) - 1) = ∛(x^{ 3} + 1 - 1) = ∛(x^{ 3}) = x g^{ -1}(g(x)) = (g(x)) ^{ 3} + 1 = (∛(x - 1)) ^{ 3} + 1 = x - 1 + 1 = x We can easily check that the graphs of functions g and g^{ -1} , shown below, are reflection of each other on the line y = x and are therefore inverse of each other.
Find the inverse of a logarithmic functionQuestion 4Find the inverse of the function h(x) = ln(x - 1) and graph f and its inverse in the same system of axes.Solution to Question 4step 1: Rewrite the function as an equation as follows y = ln(x - 1) step 2: Exchange x and y y = ln(y - 1) step 3: Solve the above for y change logarithm into exponential y - 1 = e^{x} y = e^{x} + 1 Step 4: Use inverse function notation h^{ -1} (x) = e^{x} + 1 Step 5: Check algebraically the answer h(h^{ -1}(x)) = ln(h^{ -1}(x) - 1) = ln(e^{x} + 1 - 1) = ln(e^{x}) = x h^{ -1}(h(x)) = e^{h(x)} + 1 = e^{ln(x - 1)} + 1 = x - 1 + 1 = x The graphs of functions h and h^{ -1} are shown below. The two graphs are reflection of each other on the line y = x and are therefore inverse of each other.
Question 5Find the inverse of the function m(x) = √(x + 2)Solution to Question 5step 1: Rewrite the given function as an equation y = √(x + 2) step 2: Exchange x and y x = √(y + 2) step 3: Solve the above for y raise both sides of the above equation to the power 2 (x)^{ 2} = (√(y + 2))^{ 2} x^{ 2} = y + 2 y = x^{ 2} - 2 Note the y = x^{ 2} - 2 is not a one to one and therefore not invertible. We need to restrict its domain. The domain of an inverse function is the range of the given function y = √(x + 2) which given by the interval [0 , ∞) Step 4: Use inverse function notation m^{ -1} (x) = x^{ 2} - 2 , x ≥ 0 (restricted domain) Step 5: Check algebraically the answer m(m^{ -1}(x)) = √(m^{ -1}(x) + 2) = √(x^{ 2} - 2 + 2) = √(x^{ 2}) = | x | = x because x ≥ 0 m^{ -1}(m(x)) = (m(x))^{ 2} - 2 = (√(x + 2))^{ 2} - 2 = x + 2 - 2 = x The graphs of f and f^{ -1} shown below are reflection of each other on the line y = x and are therefore inverse of each other.
Question 6Find the inverse of the function t(x) = 1 / (x - 1)Solution to Question 6step 1: Rewrite the given function as an equation y = 1 / (x - 1) step 2: Exchange x and y x = 1 / (y - 1) step 3: Solve the above for y Multiply both sides by y - 1 and simplify x(y - 1) = 1 x y - x = 1 y = (x + 1) / x Step 4: Use inverse function notation to write t^{ -1} (x) = (x + 1) / x Step 5: Check algebraically the answer t(t^{ -1}(x)) = 1 / (t^{ -1}(x) - 1) = 1 / ((x + 1) / x - 1) = x / (x + 1 - x) = x t^{ -1}(t(x)) = (t(x) + 1) / t(x) = ( 1 / (x - 1) + 1 ) / (1 / (x - 1)) = ( x / (x - 1)) / (1 / (x - 1)) = x We can check that the graphs of functions t and t^{ -1} , shown below, are reflection of each other on the line y = x and are therefore inverse of each other. |